2011
DOI: 10.1038/eye.2011.60
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of iCare tonometer and Goldmann applanation tonometry in normal corneas and in eyes with automated lamellar and penetrating keratoplasty

Abstract: Purpose To compare intraocular pressure (IOP) measurements with Goldmann applanation tonometry (GAT) and iCare tonometry in normal and post-keratoplasty corneas and to assess the influence of central corneal thickness (CCT), corneal curvature (CC), and corneal astigmatism (CA) on IOP. Methods This prospective cross-sectional study included one eye of 101 subjects with normal corneas (58 healthy subjects, 43 glaucoma); and 90 post-keratoplasty patients: 34 penetrating keratoplasties (PK); 20 automated-lamellar-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 38 publications
7
42
0
2
Order By: Relevance
“…Strikingly, Sahin et al [18] found an IOP increase of 1 mm Hg and 8 mm Hg for every 100-µm increase in CCT for the IRT and the GAT, respectively. In the present study, the deviation of the IRT readings from the GAT is only 0.097 mm Hg for every 10 µm of CCT and is comparable with the work of Salvetat et al [19] who reported a deviation of 0.09 mm Hg for every 10-µm increase in CCT. Perhaps, biomechanical properties of the cornea, namely corneal hysteresis and corneal resistance factor, are more influential on the IRT measurements than CCT [20,31,32,33].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Strikingly, Sahin et al [18] found an IOP increase of 1 mm Hg and 8 mm Hg for every 100-µm increase in CCT for the IRT and the GAT, respectively. In the present study, the deviation of the IRT readings from the GAT is only 0.097 mm Hg for every 10 µm of CCT and is comparable with the work of Salvetat et al [19] who reported a deviation of 0.09 mm Hg for every 10-µm increase in CCT. Perhaps, biomechanical properties of the cornea, namely corneal hysteresis and corneal resistance factor, are more influential on the IRT measurements than CCT [20,31,32,33].…”
Section: Discussionsupporting
confidence: 78%
“…Iliev et al [2] reported a mean difference of 1.0 ± 2.17 mm Hg (95% limit of agreement: -3.2 to 5.2) in their mixed group of patients with minor complaints and open-angle glaucoma; Kim et al [7], in their study group with various pathologies, found a mean difference of 1.92 ± 3.29 mm Hg (95% limit of agreement: -4.52 to 8.37) between the IRT and the GAT; Salim et al [15] reported a mean difference of 2.45 ± 2.12 mm Hg (95% limit of agreement: -1.79 to 6.69) in their study group consisting of glaucoma patients only; Martinez-de-la-Casa et al [16] found a median difference of 1.8 ± 2.8 mm Hg (95% limit of agreement -3.7 to 7.3) in their group consisting of subjects with glaucoma and controls; in a study of normal population, Fernandes et al [17] reported a mean difference of 1.34 ± 2.03 mm Hg (95% limit of agreement: -2.64 to 5.31) between the 2 devices. Conversely, the mean IRT was significantly lower than the GAT, with statistical significance, in a study of normal eyes and eyes with primary open-angle glaucoma [19]. Eyes with glaucoma had a higher mean IOP difference between the GAT and the IRT than healthy eyes, in this study.…”
Section: Discussionmentioning
confidence: 56%
“…In Iceland, IOP was measured with iCare TAO1 tonometer (Tiolat Oy, Helsinki, Finland). Comparisons have shown that IOP readings with iCare are clinically reproducible12 and in agreement with those obtained by Goldmann applanation tonometry 13–15…”
Section: Methodssupporting
confidence: 60%
“…Conversely, another study demonstrated that mean IOP measurement was significantly lower with RBT device compared with GAT in study of normal eyes and eyes with primary open-angle glaucoma (18). This study also found that IOP readings with RBT and GAT were significantly directly related to CCT in subjects with normal cornea.…”
Section: Discussionsupporting
confidence: 62%